Political and territorial objectives of the Kingdom of Montenegro on the eve of and during the First Balkan War - Szczepański, Wojciech (Balcanica Posnaniensia. Acta et studia, 2013)
Montenegro, the smallest of the Balkan states in the beginning of the 20th century, was especially interested in creating an anti-Turkish alliance. It aimed at attaching the fertile lands of Sandžak of Novi Pazar, Metohija and Shkodër. Finally, as a result of the I Balkan War, it managed to achieve the first two aims, only if partially, because it had to share those lands with Serbia. Montenegro did not manage to take over control of Shkodër and the surroundings inhabited mainly by Albanians. There were many reasons why Montenegro did not manage to realize its territorial aspirations: – the poor financial condition of the state of Montenegro on the eve of the war, which prevented them from gaining a strong position in the Balkan alliance and made a success in its military actions dependent on the allies, especially on Serbia; – the detrimental pressure exerted by king Nicolas I to fight at any cost for the control over Shkodër; – a conflict of interest and mistakes made by the Montenegro authorities in developing their relations with Serbia, which weighed later on the relations between Montenegro and Serbia in the period between the Balkan wars and the First World War, as well as at the time when Yugoslavia began to unite around the idea of building the common state. – not appreciating to a sufficient degree the significance of the Albanian problem and not using the possession of the North Albanian lands as a bargaining chip in the relations with neighbors, particularly with Serbia.